2017
DOI: 10.1159/000457907
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fiber Loss in Anti-VEGF Therapy for Age-Related Macular Degeneration Can Be Decreased by Anterior Chamber Paracentesis

Abstract: Purpose: To analyze peripapillary retinal nerve fiber layer thickness (RNFLT) change after long-term intravitreal anti-VEGF therapy. Patients with regular anterior chamber paracentesis (ACP) prior to intravitreal injections (IVIs) were compared to those without ACP. Methods: Neovascular age-related macular degeneration (nAMD) was treated in a pro re nata regimen with a minimum of 9 IVIs. RNFLT change was determined in spectral domain optical coherence tomography. Results: In 32 patients without ACP, mean RNFLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…It has recently been shown that intravitreal injection monotherapy did not affect peripapillary retinal NFL at least during the first year of treatment, 32 while others did not exclude an effect over 2.5 years. 33 However, together with the finding of parafoveal nasal MVAs, the issue of possible nerve fibre loss in the papillomacular bundle should be followed further.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that intravitreal injection monotherapy did not affect peripapillary retinal NFL at least during the first year of treatment, 32 while others did not exclude an effect over 2.5 years. 33 However, together with the finding of parafoveal nasal MVAs, the issue of possible nerve fibre loss in the papillomacular bundle should be followed further.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies have shown that prophylactic anterior chamber paracentesis is a safe and effective option for preventing IOP spikes after an intravitreal injection 87,113,114 . Most notably, Enders et al found a significant RNFL-loss in patients who had not undergone anterior chamber paracentesis prior to their intravitreal injections, but could not find a significant reduction in RNFL-thickness in those who did 115 . We can therefore conclude that there are several effective options for IOP prophylaxis.…”
Section: Summary Of Findingsmentioning
confidence: 92%
“…Im Februar 2017 publizierten Enders et al bei intravitrealen Injektionen mit gleichzeitiger Vorderkammerpunktion vergleichbare Langzeitergebnisse [41]. Sie hatten bei 76 AMD-Patienten ohne Glaukom, die an einem Auge wenigstens 9 intravitreale Injektionen erhalten hatten, die RNFL über 30 Monate bei 44 Augen verfolgt.…”
Section: Nachweis Eines Protektiven Effekts Der Parazentese Bei Intraunclassified